Association of venous varix and developmental venous anomaly: report of a case and review of literature. Issue 3 (12th March 2019) - Naik, Suprava; Bhoi, Sanjeev K
Abstract : Cerebral developmental venous anomalies (DVAs) are the most frequently encountered cerebral vascular malformation. Most are asymptomatic and incidentally detected. Here we present a case of DVA associated with venous varix presented with chronic headache. A 50-year-old woman presented with right hemicranial headache since 6 months. There was no neurological deficit. MRI showed a well-defined oval T2 hyperintense, T1 isointense extra-axial lesion in the right parietal region showing intense homogeneous enhancement. Prominent vascular flow void was extending from the lesion up to the deep parietal white matter. Subtle thin linear areas of blooming noted in the parietal white matter converging towards the vascular flow void. The venous sac is in communication with the cortical vein draining to the superior sagittal sinus. These MRI findings favoured a diagnosis of DVA in the right parietal lobe with prominent draining vein forming a cortical venous varix. The patient was managed conservatively with symptomatic treatment for headache.